Optimal dosing regimen of CD73 blockade improves tumor response to radiotherapy through iCOS downregulation - Pierre-Antoine Laurent; Eric Deutsch; Michele Mondini; Marine Gerbé De Thoré; Winchygn Liu; Lydia Meziani; Céline Clémenson; Marie-Catherine Vozenin (Journal for ImmunoTherapy of Cancer, 2023)
Background Irradiation (IR) and immune checkpoint inhibitor (ICI) combination is a promising treatment modality. However, local and distance treatment failure and resistance can occur. To counteract this resistance, several studies propose CD73, an ectoenzyme, as a potential target to improve the antitumor efficiency of IR and ICI. Although CD73 targeting in combination with IR and ICI has shown attractive antitumor effects in preclinical models, the rationale for CD73 targeting based on CD73 tumor expression level deserves further investigations.Methods Here we evaluated for the first time the efficacy of two administration regimens of CD73 neutralizing antibody (one dose vs four doses) in combination with IR according to the expression level of CD73 in two subcutaneous tumor models expressing different levels of CD73.Results We showed that CD73 is weakly expressed by MC38 tumors even after IR, when compared with the TS/A model that highly expressed CD73. Treatment with four doses of anti-CD73 improved the TS/A tumor response to IR, while it was ineffective against the CD73 low-expressing MC38 tumors. Surprisingly, a single dose of anti-CD73 exerted a significant antitumor activity against MC38 tumors. On CD73 overexpression in MC38 cells, four doses of anti-CD73 were required to improve the efficacy of IR. Mechanistically, a correlation between a downregulation of iCOS expression in CD4+ T cells and an improved response to IR after anti-CD73 treatment was observed and iCOS targeting could restore an impaired benefit from anti-CD73 treatment.Conclusions These data emphasize the importance of the dosing regimen for anti-CD73 treatment to improve tumor response to IR and identify iCOS as part of the underlying molecular mechanisms. Our data suggest that the selection of appropriate dosing regimen is required to optimize the therapeutic efficacy of immunotherapy–radiotherapy combinations.